Recovery from prolonged intermittent shuttle running following 9 days of ascorbic acid supplementation - Bailey, D. M.; Williams, C.; Markovitch, D.; Dean, A.; Webb, J. M. M.; Powell, J. R. (The Journal of Physiology, 2002)
The aim of this investigation was to determine whether supplementation with ascorbic acid alleviates muscle damage and aids recovery of muscle function in the days following exercise. Thirty-two males participated in this investigation, which was approved by the University Ethical Committee. The mean age, body mass and maximal oxygen uptake (O2,max) was 21.8 ± 0.2 years (mean ± S.E.M.), 82.9 ± 10.4 kg and 53.5 ± 4.6 ml kg-1 min-1, respectively. Participants were divided into two matched groups and assigned to 9 days supplementation of either ascorbic acid (AA) or a lactose placebo (PL) 800 mg day-1, in a double-blind design. On the seventh day participants completed the 90 min Loughborough Intermittent Shuttle Test (LIST), comprising six 15 min periods of intermittent running, consisting of sprinting, interspersed with periods of jogging and walking (Nicholas et al. 2000). Biochemical markers of muscle damage and oxidative stress were monitored up to 48 h post-exercise (PE). Ratings of perceived soreness and isometric maximal voluntary contraction (MVC) of the leg extensors and flexors were monitored up to 7 days PE. Data were analysed with repeated measures ANOVA. Following supplementation with AA, increases in serum myoglobin concentration from pre-exercise values (160.8 ± 14.2 ng ml-1) were lower at 1 h PE when compared with PL (300.3 ± 27.6 ng ml-1) (P < 0.01). Recovery of muscle function in the leg flexors, assessed as change in MVC from pre-exercise, was greater following AA supplementation at 96 h (103 ± 2 %) and 168 h (101 ± 4 %) when compared with PL (90 ± 6 % and 88 ± 5 %) (P < 0.05). Serum concentrations of uric acid were markedly increased 48 h PE with PL supplementation (382 ± 14 mmol l-1) compared with AA supplementation (331 ± 9 mmol l-1) (P < 0.05). Although no effect of intervention was observed, ratings of perceived soreness increased during the PE period, peaking at 24 h (5.3 ± 0.2, n = 32) (P < 0.01), as did serum creatine kinase activity (884 ± 134 U l-1, n = 32) (P < 0.01). Significant relationships were observed between change in MVC of the leg flexors immediately PE and serum myoglobin concentrations PE (r = 0.80, P < 0.05) and also with uric acid concentrations PE (r = 0.94, P < 0.05). These results would appear to support the recommendation of ascorbic acid supplementation as a means of reducing exercise-induced muscle damage, as reflected by changes in muscle function and biochemical markers of muscle damage.